Lifestyle risk Factors for early versus late onset dementia: A systematic review and meta-analysis. (30th September 2020) - Berselli, N; Adani, G; Filippini, T; Vinceti, M
Abstract: Background: Dementia is a widely prevalent and growing condition, affecting nearly 10% of people aged 60 years and older. It is a leading cause of disability entailing important economic and social costs for the population, so much so that it has been defined as a "global public health priority' from WHO in 2016. Dementia can be divided into two forms according to age of onset of the first symptoms: Early Onset Dementia (EOD - < 65 years) and Late Onset Dementia (LOD, ≥ 65 years). The differences between the two forms, and if they could be considered as separate diseases, are still not well understood. The aim of this meta-analysis was to determine if environmental-lifestyle risk factors of dementia may differ between EOD and LOD. Methods: Literature databases were searched to June 2020, to retrieve studies assessing the impact of modifiable factors in patients who had developed the first symptoms of dementia before (for EOD) or after (for LOD) 65 years. Data were then meta-analysed in order to understand the overall impact of the single factors on EOD and LOD separately. Results: The results show different effects for some risk factors as alcohol consumption (OR 2.8, 95%CI: 2.2-3.4 for EOD and OR 1.2, 95%CI: 0.9-1.5 for LOD) and brain injuries (OR 1.4, 95%CI: 1.2-1.6 for EOD, and OR 1, 95%CI: 0.6-1.4 for LOD), which appear to have more impact on EOD compared with LOD. No association with smoking for both forms of dementia emerged. The other factors considered, such as low educational attainment, socio-economic status, closeness of magnetic field, appear to have similar impact on the two forms of dementia. Conclusions: These results suggest that there may be a difference, in terms of modifiable risk factors, between the two forms of dementia, even if more research is needed on this issue. Key messages: There may be different risk factors determining EOD versus LOD onset. By modifying some environmental and lifestyle factors we could delay or prevent the onset of dementia.